Pulmonary Hypoplasia Caused by Fetal Ascites in Congenital Cytomegalovirus Infection Despite Fetal Therapy - Fujioka, Kazumichi; Morioka, Ichiro; Nishida, Kosuke; Morizane, Mayumi; Tanimura, Kenji; Deguchi, Masashi; Iijima, Kazumoto; Yamada, Hideto (Frontiers in Pediatrics, 2017)
We report two cases of pulmonary hypoplasia due to fetal ascites in symptomatic congenital cytomegalovirus (CMV) infections despite fetal therapy. The patients died soon after birth. The pathogenesis of pulmonary hypoplasia in our cases might be thoracic compression due to massive fetal ascites as a result of liver insufficiency. Despite aggressive fetal treatment, including multiple immunoglobulin administration, that was supposed to diminish the pathogenic effects of CMV either by neutralization or immunomodulatory effects, the fetal ascites was uncontrollable. To prevent development of pulmonary hypoplasia in symptomatic congenital CMV infections, further fetal intervention to reduce ascites should be considered.